The effect of aerobic training on healthy elderly women’s walking speed, step length and habitual physical activity - Resende, Thais de Lima (PAJAR - Pan American Journal of Aging Research)
This study’s main aim was to investigate whether training could increase walking speed, step length and habitual physical activity (HPA) in elderly women. This randomized controlled trial was carried out with 22 elderly women, who were first monitored for a week (heart rate and movement), had their chosen and faster walking speed determined, as well as their step rate and length, and underwent sub maximal treadmill tests. Data from monitoring were organized into 7 HPA indices. The women were randomly allocated to a control (73. 6±1. 7 years) or exercise group (75. 5±2. 9). For 12 weeks the exercisers walked 3 times a week on a treadmill at 60-65% of their predicted HRR. Controls continued with their normal routine. Post-training, all measurements were repeated. Training was associated with significant increases in step length and walking speeds. However, no significant changes in the HPA indices were found. It is concluded that the three-month aerobic training program by treadmill walking resulted in significant increases in step length and self-selected walking speeds in these healthy, independent, elderly women, however, it did not lead to increased habitual physical activity